A systematic review of older adults' request for or attitude toward euthanasia or assisted-suicide. (4th March 2021) - Castelli Dransart, Dolores Angela; Lapierre, Sylvie; Erlangsen, Annette; Canetto, Silvia Sara; Heisel, Marnin; Draper, Brian; Lindner, Reinhard; Richard-Devantoy, Stephane; Cheung, Gary; Scocco, Paolo; Gusmão, Ricardo; De Leo, Diego; et al.
Abstract: Objectives: Prevalence rates of death by euthanasia (EUT) and physician-assisted suicide (PAS) have increased among older adults, and public debates on these practices are still taking place. In this context, it seemed important to conduct a systematic review of the predictors (demographic, physical health, psychological, social, quality of life, religious, or existential) associated with attitudes toward, wishes and requests for, as well as death by EUT/PAS among individuals aged 60 years and over. Method: The search for quantitative studies in PsycINFO and MEDLINE databases was conducted three times from February 2016 until April 2018. Articles of probable relevance ( n = 327) were assessed for eligibility. Studies that only presented descriptive data ( n = 306) were excluded. Results: This review identified 21 studies with predictive analyses, but in only 4 did older adults face actual end-of-life decisions. Most studies (17) investigated attitudes toward EUT/PAS (9 through hypothetical scenarios). Younger age, lower religiosity, higher education, and higher socio-economic status were the most consistent predictors of endorsement of EUT/PAS. Findings were heterogeneous with regard to physical health, psychological, and social factors. Findings were difficult to compare across studies because of the variety of sample characteristics and outcomes measures. Conclusion: Future studies should adopt common and explicit definitions of EUT/PAS, as well as research designs (e.g. mixed longitudinal) that allow for better consideration of personal, social, and cultural factors, and their interplay, on EUT/PAS decisions.